A low expansion glass-ceramic and preparation method thereof
By increasing the Li2O content and controlling the MgO/Li2O ratio, the LiAl2SiO6 crystal phase with a negative thermal expansion coefficient is formed, which solves the problems of high viscosity and difficult melting of glass in the prior art, and achieves low expansion and fusibility of the microcrystalline glass.
Patent Information
- Application Number
- CN202310294418.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-23
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-03-23
AI Technical Summary
In the prior art, CaO and BaO co-solvents cannot be used, and the total amount of K2O and Na2O co-solvents is limited, resulting in the problem of high glass viscosity and difficult melting.
By increasing the Li2O content, more LiAl2SiO6 crystal phases with negative thermal expansion coefficients are formed, the MgO/Li2O ratio is controlled, so that the thermal expansion coefficient of the microcrystalline glass is approaching 0, and the high-temperature viscosity of the glass is reduced, thereby reducing the melting difficulty.
It effectively solves the problem that CaO and BaO co-solvents cannot be used, and the total amount of K2O and Na2O co-solvents is limited, resulting in high viscosity of glass, reducing the high-temperature viscosity of glass, and simplifying the melting process.
Smart Images

Figure CN116553833B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of low-expansion microcrystalline glass, and in particular to a low-expansion microcrystalline glass and a preparation method thereof. Background Art
[0002] In some application fields, when processing ultra-low expansion glass-ceramics into ultra-precision components, it is necessary to use acid to clean the polished surface to remove foreign matter. If the acid corrosion resistance of ultra-low expansion glass-ceramics is poor, pits will form on the surface due to acid corrosion, affecting the roughness of the ultra-smooth surface. Therefore, the acid corrosion resistance of ultra-low expansion glass-ceramics must be taken seriously. Studies have shown that the introduction of CaO and BaO components into glass-ceramics has a better fluxing effect, and compared with alkali metal oxides, the glass is not easy to become opaque and affect the transmittance during the heat treatment crystallization process.
[0003] However, CaO and BaO will not enter the crystal phase after crystallization, but will remain in the glass phase, affecting the network density of the glass phase and causing the acid corrosion resistance of the microcrystalline glass material to decrease. If alkali metal oxides K2O and Na2O are used as co-solvents to reduce the viscosity of the glass, excessive amounts will cause the glass to crystallize and become opaque, resulting in poor light transmittance. Summary of the invention
[0004] The purpose of the present invention is to provide a low-expansion microcrystalline glass and a preparation method thereof, so as to solve the technical problem that in the prior art, CaO and BaO solvents cannot be used and the total amount of K2O and Na2O solvents is limited, resulting in high glass viscosity and great difficulty in melting.
[0005] The invention discloses a low-expansion microcrystalline glass, which comprises, by weight percentage, 50-75% SiO2, 10-30% Al2O3, 1.5-10% P2O5, 5-15% Li2O, 0.5-7% ZnO, 0.5-10% MgO, 0.3-5.0% Na2O, 0.3-5.0% K2O, 1-5% TiO2 and 0.5-5% ZrO2.
[0006] Furthermore, the composition includes, by weight percentage: SiO2 56-73%, Al2O3 11-21%, P2
[0007] O5 1.5~5.5%, Li2O 7~11%, ZnO 0.5~5%, MgO 1~5%, Na2O 0.3~3.0%, K2O0.3~2.0%, TiO2 1~4%, ZrO2 0.5~3%.
[0008] Furthermore, the composition includes, by weight percentage: SiO2 58-70%; and / or Al2O3 14-20%; and / or P2O5 3-6%; and / or Li2O 8-11%.
[0009] Furthermore, (ZnO+Mg+Li2O+Al2O3+P2O5+SiO2) / (Al2O3+P2O5+SiO2) is 1.10-1.20, preferably 1.115-1.175, more preferably 1.13-1.17; and / or ZnO / Li2O is 0.04-0.35, preferably 0.08-0.21.
[0010] Furthermore, the total amount of Na2O+K2O is 0.3-5.0% by weight; and / or the total amount of TiO2+ZrO2 is 2-5% by weight.
[0011] Furthermore, the coefficient of thermal expansion is -10×10 -8 ~10×10 -8 / ℃, preferably -5×10 -8 ~5×10 -8 / ℃; and / or Knoop hardness of 550×10 7 ~575×10 7 Pa, preferably 545×10 7 ~565×10 7 Pa; and / or the exothermic peak temperature range of the glass differential thermal curve is 776 to 1106°C, preferably 858 to 1002°C.
[0012] The second object of the present invention is to protect a method for preparing a low-expansion microcrystalline glass. During the crystallization process, the matrix glass is kept warm at a temperature range of 720-770°C, then heated to 780-830°C and kept warm again.
[0013] Furthermore, the method further comprises the following steps: 1) mixing materials, 2) melting, 3) preparing matrix glass, and 4) crystallizing.
[0014] Furthermore, the specific steps are: 1) weighing each raw material according to the formula composition of the low expansion glass-ceramics, mixing the raw materials evenly to form a mixture; 2) adding the mixture to a melting furnace (electric furnace or gas furnace), and heating it to 1500-1580°C for melting; 3) after the mixture is completely melted, raising the furnace temperature to 1580-1650°C for clarification for 5-8 hours, and then stirring the glass liquid at 1400-1450°C for 2-4 hours, and then pouring the prepared glass liquid into a mold for rapid cooling and shaping, and then placing it in an annealing furnace for slow cooling to obtain a matrix glass; 4) forming the matrix glass into a low expansion glass-ceramics through a crystallization process.
[0015] The third object of the present invention is to protect a glass preform, which is made of the low-expansion glass-ceramic mentioned above or made of the low-expansion glass-ceramic obtained by the above preparation method.
[0016] A fourth object of the present invention is to protect an optical element, which is made of the low-expansion glass-ceramic described above, or a low-expansion glass-ceramic obtained by the above-mentioned preparation method, or the above-mentioned glass preform.
[0017] The fifth purpose of the present invention is to protect optical instruments, which are made of the above-mentioned low-expansion microcrystalline glass, or made of a low-expansion microcrystalline glass obtained by the above-mentioned preparation method, or made of the above-mentioned glass preform, or made of the above-mentioned optical element.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. Further increase the Li2O content to form more LiAl2SiO6 crystal phases with negative thermal expansion coefficients. By controlling the MgO / Li2O ratio, the thermal expansion coefficient of glass-ceramics can be made close to 0. The increase of Li2O can further reduce the high-temperature viscosity of the glass and reduce the difficulty of melting, thus solving the problem of not being able to use CaO and BaO solvents, the total amount of K2O and Na2O solvents being limited, and the high viscosity of the glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only represent some embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work. Figure 1 This is the XRD diffraction pattern of the glass-ceramics No. 12 of Example 1 of the present invention. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.
[0022] SiO2 is a network former of the matrix glass. Most of it enters the β-quartz solid solution crystal phase after heat treatment, and a small amount exists in the residual glass phase, which is the main component of the glass phase. In the present invention, too much SiO2 content will increase the high temperature viscosity of the glass, making it difficult to clarify, remove bubbles and stir and homogenize the glass. Too little SiO2 content will cause the hardness of the glass to decrease. Therefore, the content range of SiO2 in the present invention is 50-75%, preferably 56-73%, and more preferably 58-70%.
[0023] Al2O3 is a network intermediate component of the matrix glass. After heat treatment, most of it enters the β-quartz solid solution crystal phase, and a small amount exists in the residual glass phase. Too much Al2O3 content will increase the difficulty of glass materialization, increase high temperature viscosity, and make glass clarification and homogenization difficult. Too little Al2O3 content will make glass crystallization difficult and difficult to form transparent microcrystalline glass. Therefore, the content range of Al2O3 in the present invention is 10-30%, preferably 11-21%, and more preferably 14-20%.
[0024] P2O5 improves the solubility of ZrO2 in glass and avoids the formation of ZrO2 stones in the matrix glass. After crystallization, the structure of AlPO4 replaces SiO2 in the crystal phase. Therefore, when the content of P2O5 increases, Al2O3 should also increase accordingly, and SiO2 decreases accordingly, which is equivalent to replacing SiO2 with Al(PO3)3 in the formula design. The melting temperature of Al(PO3)3 is much lower than that of SiO2, which is beneficial to lowering the melting temperature of glass. Therefore, too little P2O5 is not conducive to the introduction of the nucleating agent ZrO2, and will make the melting temperature of the glass too high. However, P2O5 is a volatile component, and too much introduction is not conducive to stable batch preparation, and too little SiO2 will deteriorate the hardness of the microcrystalline glass. Therefore, the content range of P2O5 in the present invention is 1.5-10%, preferably 1.5-5.5%, and more preferably 3-6%.
[0025] Li2O can reduce the high temperature viscosity of glass and is also an essential component for the formation of β-quartz solid solution. After heat treatment, all Li2O enters the crystal phase. Too much content will cause the glass to crystallize easily. During the molding and cooling process, a thick crystallization layer will quickly form on the surface. Due to the large difference in thermal expansion coefficient with the internal glass phase, it is easy to cause the glass to burst, which is not conducive to the molding process control of large-size products, and is not conducive to uniform crystallization during heat treatment; too little Li2O content will increase the difficulty of glass materialization, and high temperature
[0026] The viscosity increases, the glass becomes difficult to clarify and homogenize, and it is difficult to form β-quartz solid solution crystallites during heat treatment, which leads to easy phase separation during glass heat treatment and reduced transmittance. Therefore, the Li2O content in the present invention is in the range of 5-15%, preferably in the range of 7-11%, and more preferably in the range of 8-11%.
[0027] ZnO can reduce the high temperature viscosity of glass and will form Zn after heat treatment. 0.5 The thermal expansion coefficient of AlSi2O6 crystal phase is negative. Therefore, after the introduction of ZnO, the Li2O content can be reduced accordingly, so that the peak temperature of the differential thermal curve of the glass is increased, and the crystallization rate is slowed down, which is beneficial to suppress the surface crystallization during the molding cooling process and is beneficial to the crystallization control during the heat treatment process. If too much is introduced, Li2O needs to be greatly reduced accordingly, so that the high-temperature viscosity of the glass is too large and the transmittance of the microcrystalline glass is reduced. Therefore, the ZnO content in the present invention is in the range of 0.5-7%, preferably in the range of 0.5-3%, and ZnO / Li2O is 0.04-0.35, preferably 0.08-0.21.
[0028] MgO can effectively reduce the high temperature viscosity of glass, but it will form Mg after heat treatment. 0.5 The thermal expansion coefficient of AlSi2O6 crystal phase is positive, which will cause the thermal expansion coefficient to deviate too much from 0 in the positive direction. Therefore, it is necessary to increase the Li2O and ZnO components accordingly to form more LiAl Si2O6 and ZnO with negative thermal expansion coefficients. 0.5 AlSi2O6 and Mg 0.5 AlSi2O6 matches, making the thermal expansion coefficient approach 0, and achieving the purpose of further reducing the viscosity of the glass. However, too much MgO will make the total amount of Li2O, ZnO, and MgO too much, resulting in a decrease in the peak temperature of the differential thermal curve of the glass, a too fast crystallization rate, and a too thick surface crystallization layer will be formed during the molding process, which is not conducive to the uniform growth of microcrystals during the crystallization process; too little MgO will make the total amount of Li2O, ZnO, and MgO too little, which will not only increase the difficulty of melting the glass, but also reduce the transmittance of the microcrystalline glass. Therefore, the MgO content in the present invention is in the range of 0.5-7%, preferably in the range of 1-5%, and (ZnO+Mg+Li2O+Al2O3+P2O5+SiO2) / (Al2O3+P2O5+SiO2): 1.10-1.20, preferably 1.115-1.175, and more preferably 1.13-1.17.
[0029] Na2O and K2O are fluxing agents, which are beneficial to lowering the melting temperature of raw materials, reducing the high-temperature viscosity of glass, and are beneficial to clarifying, removing bubbles and stirring and homogenizing. Introducing too much will increase the erosion of the crucible by the glass liquid, and the heat treatment process will easily form NaAlSi2O6 and KAlSi2O6 hot-melt quartz crystal phases, affecting the transmittance of the microcrystalline glass. Or too much Na2O and K2O exist in the residual glass phase, affecting the acid corrosion resistance of the microcrystalline glass. Therefore, in the present invention, the Na2O content ranges from 0.3 to 5.0%, preferably 0.3 to 3.0%, the K2O content ranges from 0.3 to 5.0%, preferably 0.3 to 2.0%, and the total amount of Na2O + K2O ranges from 0.3 to 5.0%.
[0030] In the present invention, TiO2 and ZrO2 are crystal nucleating agents, which can promote the formation of β-quartz solid solution. The total amount of TiO2 and ZrO2 is controlled at 2-5%. Too high a content will lead to too fast a glass crystallization rate, which is not conducive to the molding of size glass. Too little content will easily lead to too large a grain size, affecting the transmittance of microcrystalline glass. The range of TiO2 is 1-5%. Too much will cause serious coloring of the glass, which will be yellow-brown after crystallization and reduce the transmittance. Too little will require a corresponding increase in ZrO2, while too much ZrO2 will increase the difficulty of melting the raw materials. Therefore, the range of ZrO2 is 0.5-5%, preferably 0.5-3%.
[0031] Next, the properties of the low-expansion glass-ceramics of the present invention will be described.
[0032] <Crystalline content>
[0033] The XRD diffraction peaks were compared with the database spectrum, and the crystallinity was obtained by calculating the proportion of the crystalline phase diffraction intensity in the overall spectrum intensity, and was internally calibrated by using pure quartz crystals.
[0034] The crystal content of the microcrystalline glass of the present invention is greater than 90%, wherein the XRD diffraction pattern of the microcrystalline glass of Example 12 is as follows: Figure 1 shown.
[0035] <Coefficient of Thermal Expansion>
[0036] The thermal expansion coefficient (α) of the glass-ceramics of the present invention is measured at 0 to 50° C. according to the method specified in GB / T 7962.16-2010.
[0037] The thermal expansion coefficient (α) of the microcrystalline glass of the present invention is -10×10 -8 ~10×10 -8 / ℃, preferably -5×10 -8 ~5×10 -8 / ℃.
[0038] <Knoop hardness>
[0039] The Knoop hardness (H K ) Tested according to the method specified in GB / T 7962.18-2010.
[0040] The Knoop hardness (H K ) is 550×10 7 ~575×10 7 Pa, preferably 545×10 7 ~565×10 7 Pa.
[0041] <530nm Transmittance>
[0042] The 530nm transmittance of the microcrystalline glass of the present invention is tested according to the method specified in GB / T 7962.12-2010.
[0043] The transmittance at 530 nm of a 10 mm thick sample of the microcrystalline glass of the present invention is 80% to 91%, preferably 82% to 91%.
[0044] <Differential Thermal Curve>
[0045] The differential thermal curve of the glass of the present invention is tested by using a NETZSCH DSC 404C differential thermal instrument.
[0046] The exothermic peak temperature range of the differential thermal curve of the glass of the present invention is 776-1106°C, preferably 858-1002°C.
[0047] [Method for producing low expansion glass-ceramics]
[0048] The manufacturing method of the low expansion glass-ceramics of the present invention is as follows: 1) weighing each raw material according to the formula composition of the low expansion glass-ceramics, and mixing the raw materials uniformly to form a mixture; 2) adding the mixture to a melting furnace (electric furnace or gas furnace), and heating it to 1500-1580°C for melting; 3) after the mixture is completely melted, the furnace temperature is raised to 1580-1650°C for clarification for 5-8 hours, and then the glass liquid is stirred at 1400-1450°C for 2-4 hours, and then the prepared glass liquid is poured into a mold for rapid cooling and shaping, and then placed in an annealing furnace for slow cooling to obtain a matrix glass; 4) the matrix glass is subjected to a crystallization process to form a low expansion glass-ceramics. The crystallization process is to keep the matrix glass at a temperature range of 720-770°C for 2-4 hours, and then heat it to 780-830°C for 2-4 hours.
[0049] In some embodiments, if crystallization occurs on the surface of the matrix glass during the forming process, the surface crystallization layer of the matrix glass is ground off to avoid uneven distribution of crystal production during the glass crystallization process.
[0050] Example
[0051] In order to further clearly illustrate and describe the technical solution of the present invention, the following non-limiting examples are provided.
[0052] This embodiment adopts the manufacturing method of the low expansion glass-ceramics to obtain low expansion glass-ceramics having the composition shown in Tables 1 to 3. The components in the embodiments in Tables 1 to 3 are all expressed in weight percentage. In addition, the properties of the glass-ceramics of each embodiment are measured by the testing method described in the present invention, and the measurement results are shown in Tables 1 to 3.
[0053] Table 1
[0054]
[0055]
[0056] Table 2
[0057]
[0058]
[0059] Table 3
[0060]
[0061]
[0062]
[0063] The above are the implementation methods listed in this embodiment, but this embodiment is not limited to the above optional implementation methods. Those skilled in the art can arbitrarily combine the above methods to obtain other various implementation methods. Anyone can derive other various forms of implementation methods under the inspiration of this embodiment. The above specific implementation methods should not be understood as limiting the scope of protection of this embodiment. The scope of protection of this embodiment shall be based on the definition in the claims, and the description can be used to interpret the claims.
Claims
1. A low expansion glass-ceramic, characterized in that: Calculated by weight percentage, it includes: SiO2 50-75%, Al2O3 10-30%, P2O5 1.5-10%, Li2O 5-15%, ZnO 0.5-7%, MgO 0.5-10%, Na2O 0.3-5.0%, K2O0.3-5.0%, TiO2 1-5%, ZrO2 0.5-5%, ZnO / Li2O is 0.108-0.21, (ZnO+MgO+Li2O+Al2O3+P2O5+SiO2) / (Al2O3+P2O5+SiO2) is 1.156-1.20, and it does not contain CaO and BaO.
2. The low expansion glass-ceramic according to claim 1, characterized in that: Calculated by weight percentage, it includes: SiO2 56~73%, Al2O3 11~21%, P2O5 1.5~5.5%, Li2O 7~11%, ZnO 0.5~5%, MgO 1~5%, Na2O0.3~3.0%, K2O 0.3~2.0%, TiO2 1~4%, and ZrO2 0.5~3%.
3. The low expansion glass-ceramics according to claim 2, characterized in that: Calculated by weight percentage, it includes: SiO2 58-70%; and / or Al2O3 14-20%; and / or: P2O5 3-5.5%; and / or: Li2O 8-11%.
4. A low expansion glass-ceramic according to any one of claims 1 to 3, characterized in that: (ZnO+MgO+Li2O+Al2O3+P2O5+SiO2) / (Al2O3+P2O5+SiO2) is 1.156-1.175; and / or ZnO / Li2O is 0.12-0.
21.
5. The low expansion glass-ceramics according to claim 4, characterized in that: (ZnO+MgO+Li2O+Al2O3+P2O5+SiO2) / (Al2O3+P2O5+SiO2) is 1.156-1.17; and / or ZnO / Li2O is 0.12-0.
208.
6. The low expansion glass-ceramics according to any one of claims 1 to 3, characterized in that: The total amount of Na2O+K2O is 0.6-5.0% by weight; and / or the total amount of TiO2+ZrO2 is 2-5% by weight.
7. The low expansion glass-ceramics according to any one of claims 1 to 3, characterized in that: The thermal expansion coefficient is -10×10 -8 ~10×10 -8 / ℃; and / or Knoop hardness of 550×10 7 ~575×10 7 Pa; and / or the 530nm transmittance of a 10mm thick sample is 80% to 91%; and / or the exothermic peak temperature range of the glass differential thermal curve is 776 to 1106°C.
8. The low expansion glass-ceramics according to claim 7, characterized in that: The thermal expansion coefficient is -5×10 -8 ~5×10 -8 / ℃; and / or Knoop hardness of 550×10 7 ~565×10 7 Pa; and / or the 530nm transmittance of a 10mm thick sample is 82% to 91%; and / or the exothermic peak temperature range of the glass differential thermal curve is 858 to 1002°C.
9. A method for preparing low expansion glass-ceramics according to any one of claims 1 to 8, characterized in that: In the crystallization process, the matrix glass is kept at a temperature range of 720-770°C, then the temperature is raised to 780-830°C and kept again.
10. A glass preform, characterized in that: It is made of a low-expansion glass-ceramic as described in any one of claims 1 to 8 or a low-expansion glass-ceramic obtained by the preparation method described in claim 9.
11. An optical element, characterized in that It is made of a low expansion glass-ceramic as described in any one of claims 1 to 8, or a low expansion glass-ceramic obtained by the preparation method described in claim 9, or a glass preform as described in claim 10.
12. An optical instrument, characterized in that It is made of a low expansion glass-ceramic as described in any one of claims 1 to 8, or a low expansion glass-ceramic obtained by the preparation method described in claim 9, or a glass preform as described in claim 10, or an optical element as described in claim 11.
Citation Information
Patent Citations
Anti-radiation lithium-aluminum-silicate system low-expansion window glass and machining process thereof
CN105948516A